2016
DOI: 10.7860/jcdr/2016/23787.8900
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biochemical Markers Serum Amylase and Serum Lipase for the Assessment of Pancreatic Exocrine Function in Diabetes Mellitus

Abstract: Our study clearly demonstrated that in type 1 and type 2 DM, there was increase in fasting blood sugar with decrease in serum amylase and serum lipase which signifies the derangement of endocrine-exocrine axis of the pancreas. Serum amylase and serum lipase can be used as biochemical markers for assessment of pancreatic exocrine function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…In a seminal report by Coppetiers et al, in situ HLA-tetramer staining revealed CD8 + T cells specific for islet antigens -insulin, IGRP and IA-2 -within insulitic lesions, though the persistence of β-cell mass and number of islet antigen-reactive T cell specificities varied across donors in accordance with disease duration [56]. Similarly, CD4 + T cells isolated from the islets of organ donors with recent-onset T1D exhibited reactivity to multiple GAD65 epitopes, as well as proinsulin [76][77][78][79][80][81][82][83][84][85][86][87][88][89][90] and IA-2 545-562 , measured by antigen-stimulated IFNγ secretion [57]. Moreover, islet-infiltrating CD4 + T cell clones, when reconstructed to express T cell receptors (TCRs) as transductants, have been identified to respond to proinsulin, C-peptide amino acids 19-35 (C:19-35), and insulin B:9-23 [48].…”
Section: Immunological Determinants Of Human T1dmentioning
confidence: 99%
See 2 more Smart Citations
“…In a seminal report by Coppetiers et al, in situ HLA-tetramer staining revealed CD8 + T cells specific for islet antigens -insulin, IGRP and IA-2 -within insulitic lesions, though the persistence of β-cell mass and number of islet antigen-reactive T cell specificities varied across donors in accordance with disease duration [56]. Similarly, CD4 + T cells isolated from the islets of organ donors with recent-onset T1D exhibited reactivity to multiple GAD65 epitopes, as well as proinsulin [76][77][78][79][80][81][82][83][84][85][86][87][88][89][90] and IA-2 545-562 , measured by antigen-stimulated IFNγ secretion [57]. Moreover, islet-infiltrating CD4 + T cell clones, when reconstructed to express T cell receptors (TCRs) as transductants, have been identified to respond to proinsulin, C-peptide amino acids 19-35 (C:19-35), and insulin B:9-23 [48].…”
Section: Immunological Determinants Of Human T1dmentioning
confidence: 99%
“…result in the generation and presentation of neoantigens [67]. Indeed, T cells reactive to post-translationally modified proteins such as a citrullinated form of GRP78 292-305 and islet amyloid polypeptide (IAPP) [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84] , as well as defective ribosomal insulin gene products (DRiPs) and peptides formed from the fusion of insulin C-peptide fragments with chromogranin A or IAPP (termed hybrid insulin peptides, HIPs) have been isolated from the islets of T1D donors [57,68]. Thus, β-cells may play a role in their own destruction through stress-induced protein processing defects, which may serve to induce a critical break in tolerance or to exacerbate existing pathology by expanding the β-cell antigenic repertoire.…”
Section: Immunology Of Diabetes Society Review Series: Insights Into mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, serum amylase activity is linked to the islet β cell function in type 2 diabetes patients . In fact, serum amylase has been regarded as a biochemical marker to assess pancreatic exocrine function in patients with diabetes mellitus …”
Section: Introductionmentioning
confidence: 99%
“…3 In fact, serum amylase has been regarded as a biochemical marker to assess pancreatic exocrine function in patients with diabetes mellitus. 4 The ABO blood type antigens (A, B, and H determinants) are glycoproteins presenting human blood types and are widely distributed on red blood cell surface and normal tissue throughout the body. 5 Several studies have found that inherited blood group antigens were associated with disease risk such as cardiovascular disease, thrombotic vascular disease and stroke.…”
Section: Introductionmentioning
confidence: 99%